Comparison of the Efficacy of Intravenous and Intramuscular Lornoxicam for the Initial Treatment of Acute Renal Colic: A Randomized Clinical Trial - Soylu, Ahmet; Sarier, Mehmet; Altunoluk, Bulent; Soylemez, Haluk; Baydinc, Yasar Can (Urology Journal, 2019)
Purpose: We aimed to find out if there was any difference between intramuscular and intravenous administration of lornoxicam in terms of efficacy and side effects. Materials and Methods: This study was a single-blind parallel-group randomized clinical trial. A total of 51 patients who were diagnosed with acute renal colic at our clinic were included in the study. Pain severity prior to treatment was rated using the Visual Analogue Scale (VAS). Patients were randomized into 2 groups: Group 1 (n = 27) received intramuscular 8mg lornoxicam and Group 2 (n=24) received intravenous 8mg lornoxicam. Pain severity was reassessed 30 minutes after the treatment. Pre- and post-treatment VAS scores and the mean change in the VAS scores of the 2 groups were statistically compared. Results: The mean VAS scores decreased significantly from 7.65 to 2.07 in Group 1, from 7.96 to 1.38 in Group 2, and from 7.79 to 1.75 in total (P < 0.001). No statistically significant difference was observed between Groups 1 and 2 in terms of VAS score reduction (P = 0.128). None of the patients suffered any side effects except for 1 (2%) patient who had dyspepsia. Conclusion: Parenteral lornoxicam provides significant pain relief in patients with acute renal colic. However, no significant difference was found between intramuscular and intravenous administration in terms of analgesic efficacy.